Increased Platelet-derived Microparticles Counts is Correlated with Elevated Blood LDL Cholesterol in Acute Myocardial Infarction - Kelvin Supriami; Ira Puspitawati; Dyah Samti Mayasari; Anggoro Budi Hartopo (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Platelet-derived microparticles (PDMPs) and low-density lipoprotein (LDL) cholesterol are contributing factors to acute myocardial infarction (AMI). However, the association between LDL cholesterol and PDMPs in AMI has not fully discovered. This study assessed the correlation between these two parameters in patients diagnosed with AMI.METHODS: This was an observational cross-sectional study involving 95 subjects with AMI. The blood measurement of PDMPs counts and LDL cholesterol levels were conducted concomitantly within 24 hours of admission. PDMPs count was analyzed by flow-cytometry method, meanwhile the LDL cholesterol was measured with enzymatic and colorimetric methods. For further analysis, subjects were further divided into LDL cholesterol level ≥130 mg/dL and <130 mg/dL. A statistical test was conducted for a correlative and comparative analyses.RESULTS: A correlative analysis to assess the association between PDMPs counts and LDL cholesterol level depicted a low but significant positive correlation (r=0.231, p=0.024). Furthermore, mean PDMPs counts was significantly higher in subjects with LDL cholesterol level ≥130 mg/dL compared to LDL cholesterol level <130 mg/dL (12,499.59 (95% CI: 8,507.44-16,491.74) counts/μL vs. 9,267.23 (95% CI: 4,445.45-14,089.01) counts/μL; p=0.039).CONCLUSION: There was a significant correlation between PDMPs counts and LDL cholesterol levels in AMI. A significantly increased PDMPs counts were found in subjects with LDL cholesterol level ≥130 mg/dL. Therefore, it is recommended to measure PDMPs in patients with high LDL cholesterol levels as both might be significant AMI biomarkers.KEYWORDS: acute myocardial infarction, LDL-cholesterol, platelet microparticles, platelet activation